Tax Compliance Strategies in Indonesian Public Companies: A Comparative Analysis of State Tax Law and Islamic Business Law - Yeni Elfiza Abbas; Latifah Aulia; Bekim Maksuti (Hikmatuna : Journal for Integrative Islamic Studies, 2026)
Taxes are the primary source of state revenue and play a vital role in financing national development in Indonesia. Under the self-assessment tax system, corporate tax compliance remains a major challenge, as companies often employ legal tax planning strategies to reduce their tax burden. This issue is significant not only from the perspective of state tax law but also within Islamic business law, which emphasizes justice, transparency, and ethical responsibility in economic activities. This study aims to analyze tax compliance strategies in Indonesian public companies through a comparative perspective of state tax law and Islamic business law by examining the influence of Fixed Asset Intensity, Debt-to-Equity Ratio (DER), and Current Ratio (CR) on tax avoidance, with Company Size as a moderating variable. Using a quantitative approach, this study analyzes secondary data from 29 companies listed on the Indonesia Stock Exchange during 2020–2024. The findings show that Fixed Asset Intensity significantly reduces the Effective Tax Rate (ETR), while DER and CR significantly increase ETR. Company Size strengthens the relationship between Fixed Asset Intensity and ETR but weakens the effects of DER and CR. The novelty of this study lies in integrating legal and ethical perspectives by comparing state tax law and Islamic business law in understanding corporate tax compliance. These findings provide important implications for policymakers, tax regulators, and corporate governance in promoting a fairer and more accountable taxation system.